2009
DOI: 10.1007/s00701-009-0568-y
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted anterior lumbar interbody fusion (ALIF) using retroperitoneal approach

Abstract: Although retroperitoneal approach for spinal fusion has never been attempted with robotic surgical system, we could demonstrate the possibility with swine model. Further studies and development of appropriate instruments will bring minimally invasive spine surgery to a new era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…The few applications to date have been largely restricted to spinal instrumentation. 2,9,17,27 The clinical, institutional, and economic benefits of minimally invasive surgery have been extensively described in the neurosurgical literature. 13,14,21,24 The 2 cases featured in this report demonstrate that robot-assisted thoracoscopic resection is an effective therapy for certain paravertebral schwannomas in both the high superior and low inferior posterior mediastinum with excellent perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The few applications to date have been largely restricted to spinal instrumentation. 2,9,17,27 The clinical, institutional, and economic benefits of minimally invasive surgery have been extensively described in the neurosurgical literature. 13,14,21,24 The 2 cases featured in this report demonstrate that robot-assisted thoracoscopic resection is an effective therapy for certain paravertebral schwannomas in both the high superior and low inferior posterior mediastinum with excellent perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has described some of the da Vinci system's disadvantages based on our previous, preclinical work [13,16] , but the details of its current limitations came into clearer view after our first attempt at a clinical intervention. The lack of instruments for bony dissection is the first limitation.…”
Section: Discussionmentioning
confidence: 99%
“…We followed this work with cadaver work in the spine [13] and then proceeded with this case under an IRB protocol. In addition, our group has carefully used the da Vinci robot in applications in the lumbar spine as well [16] . The experience of this surgery, invaluable as a source of improvements and ideas, has clarified limitations of the da Vinci robot and highlighted its capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 illustrates the variety of cadaveric studies that have been performed and their characteristics. 18,19,21,[25][26][27]38,40 Whereas many published studies consisted of 1-2 cadavers, Togawa et al 42 reported on the placement of lumbosacral pedicle screws, translaminar facet screws, and was assessed separately; they had all been placed successfully, with an overall average deviation of 1.03 ± 0.59 mm. In the translaminar facet instrumentation surgery, the overall average K-wire deviation was 1.05 ± 0.56 mm.…”
Section: Cadaveric Studies Of Robot-assisted Spine Surgerymentioning
confidence: 99%